Laser induced breakdown spectroscopy for bone and cartilage differentiation - ex vivo study as a prospect for a laser surgery feedback mechanism - Mehari, Fanuel; Rohde, Maximilian; Knipfer, Christian; Kanawade, Rajesh; Klämpfl, Florian; Adler, Werner; Stelzle, Florian; Schmidt, Michael (Biomedical Optics Express, 2014)
Laser surgery enables for very accurate, fast and clean modeling of tissue. The specific and controlled cutting and ablation of tissue, however, remains a central challenge in the field of clinical laser applications. The lack of information on what kind of tissue is being ablated at the bottom of the cut may lead to iatrogenic damage of structures that were meant to be preserved. One such example is the shaping or removal of diseased cartilaginous and bone tissue in the temporomandibular joint (TMJ). Diseases of the TMJ can induce deformation and perforation of the cartilaginous discus articularis, as well as alterations to the cartilaginous surface of the condyle or even the bone itself. This may result in restrictions of movement and pain. The aim of a surgical intervention ranges from specific ablation and shaping of diseased cartilage, bone or synovial tissues to extensive removal of TMJ structures. One approach to differentiate between these tissues is to use Laser Induced Breakdown Spectroscopy (LIBS). The ultimate goal is a LIBS guided feedback control system for surgical laser systems that enables real-time tissue identification for tissue specific ablation. In the presented study, the authors focused on the LIBS based differentiation between cartilage tissue and cortical bone tissue using an ex-vivo pig model.